Pengaruh Strategi Pemasaran Pada Tingkat Laba Penjualan Minyak Solar non Subsidi PT. Patra Andalas Sukses Jambi - Subhan Subhan (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2019)
This research aims to examine the effect of marketing mix strategies consisting of price, product, place, and promotion on the level of company profit, especially in the sales of non-diesel oil at PT Andalas Sukses Jambi. The method used is triangulation and descriptive qualitative methods with the purposive samplingmethod. The results showed that the Marketing Mix Strategy in increasing the company's profit PT. Patra Andalas Sukses Jambi, however, the decline in profitsthat occurred in the company was a result of the increased portion of accounts receivable in the balance sheet